Gambaran Penjualan dan Investası Obat Bermerek Apotek “X” Kelurahan Karang Anyar Kota Tarakan dengan Metode ABC Tahun 2022 - Akbar Syahputra; Benazir Evita Rukaya; Syuhada Syuhada (Politeknik Kaltara, 2024)
Effective drug management requires careful inventory control to prevent problems with shortages or excess stock which can be detrimental to both the pharmacy and consumer service. This research aims to identify the percentage of drugs based on sales and investment transactions using the ABC method at Pharmacy